Spatial Dynamics and Determinants of Population Urbanization in the Upper Reaches of the Yellow River - Zhao, Lianchun; Zhao, Chengzhang; Huang, Jiajing (Land (Basel), 2022)
The spatiotemporal evolution of population urbanization and its relationship with economic variables are important aspects of socioeconomic research and essential for revealing the mechanism of urban construction and evolution. To study the spatial heterogeneity and influencing mechanisms of population urbanization in the upper reaches of the Yellow River, this study investigated the spatial distribution and dynamic evolution of population urbanization using nuclear density analysis, exploratory spatial data analysis and the geographical detector model. The results showed that the rate of population urbanization in the upper reaches of the Yellow River increased annually since 2000 and that the nuclear density curve changed from a single–peaked mode in 2000 to a double–peaked mode in 2018. The spatial distribution of the population urbanization level was uneven, that is, high in the north and low in the south, with substantial spatial agglomeration and spatial autocorrelation. The main distribution of hot spots was in the Yinchuan area in the north, while cold spots were distributed mainly in the south. Analysis revealed that changes in population urbanization level were mainly attributable to the influence of economic and employment opportunities, such as regional GDP, GDP per capita, proportion of tertiary industry in GDP, and total retail sales of consumer goods.